MICROBIAL STRAIN IMPROVEMENT FOR OVERPRODUCTION OF INDUSTRIAL PRODUCTS - Goraya, Anum; Asghar, Fatima; Javaid, Ifrah; Ali, Sikander (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Microbes generate a wide range of products that are of interest to human beings. These products are produced in low concentrations because microbe regulates its expenditure of energy efficiently to maximise its growth. By using metabolic and genetic engineering techniques these products can be overproduced. Strain improvement has been a hallmark of industrial processes for a long time because it is necessary to make the industrial processes more efficient and cost effective. Overproduction of primary metabolites and secondary metabolites is a complicated process therefore a prerequisite of strain improvement is having knowledge of microbe’s physiology and pathway regulatory controls. However, current advances in gene manipulation techniques have made it easier to modify the strain. This review highlights different techniques and strategies that can be utilised to manipulate microorganisms into generating maximum titre of the desired industrial product.